Itinerário de um poeta : Sérgio Capparelli e a poesia infantil e juvenil - Fabretti, Lígia Maria (2013)
This research has as an objective to analyze Sérgio Capparelli's poetry for the past thirty years, since his publishing Boi da cara preta (1981) until his last work, A lua dentro do coco (2010). Considering the selected texts, this work has aimed to verify the contemporary author's trajectory by identifying the developed themes, textual features, esthetic and imagistic elements as well. Analysis consisted a twelve poetry book corpus which were destined to infant and juvenile public. The research on author's work, the corpus analysis and Capparelli's interview propitiated the answers required for this project which made possible a point of view on Capparelli's literary work, who significantly contributed to its organization and production recognition. This also remarked its relevance on Brazilian infant-juvenile literature, with a special regard to lyric. In order to give a theoretical support to this work, it has been used Erza Pound (1885-1972), Thomas Stearns Eliot (1888 -1965) Antonio Candido (1918-), Johan Huinzinga (1872-1945), Hans Robert Jauss (1921-1997), Octavio Paz (1914-1998) and Hugo Friedrich (1904-1978), historians and Brazilian infant-juvenile literary critics such as como Regina Zilberman, Maria da Glória Bordini, Vera Teixeira de Aguiar and João Luís Ceccantini were also used as references to this work.